International investments and its role in the economy of the Republic of Kazakhstan - Kanabekova, M.A.; Madenova , A.A. (BUKETOV BUSINESS REVIEW, 2018)
The economy of Kazakhstan in stable economic growth. This was influenced by a number of economic factors such as: the transformation of the planned administrative system, the entry into the economy of the following market mechanisms: arbitrary prices, privatize state property, demonopolize the economy, develop competition, liberalize foreign economic activities, reform the banking and financial system, Investment actions. In the current development of Kazakhstan’s economy, the importance of international investment is important. We have seen a rapid growth in the volume of international investment since independence. There is a development of the world economy, on an equal footing with foreign investments, its rates exceed the growth rates of international trade. All countries, despite the economic degree of development, in order to achieve economic growth, develop methods and ways of increasing international investment. To have capital, innovative technologies, qualified human resources and the practice of effective organization and management play an important role in the competitiveness of the enterprise and, accordingly, in macroeconomic situations, improve the economic performance of the country. But a lot of countries are interested in the investment and it needs to be taken into account that the competition is quite strong. Therefore, now the study of international investment is an urgent issue. The article proposes conclusions and proposals in the following areas: for the regulation of financial and credit relations; for the development of investment activities.